1993
DOI: 10.1083/jcb.123.3.513
|View full text |Cite
|
Sign up to set email alerts
|

The cell proliferation-associated antigen of antibody Ki-67: a very large, ubiquitous nuclear protein with numerous repeated elements, representing a new kind of cell cycle-maintaining proteins.

Abstract: Abstract. The antigen defined by mAb Ki-67 is a human nuclear protein the expression of which is strictly associated with cell proliferation and which is widely used in routine pathology as a "proliferation marker" to measure the growth fraction of cells in human tumors. Ki-67 detects a double band with apparent molecular weights of 395 and 345 kD in immunoblots of proteins from proliferating cells. We cloned and sequenced the full length eDNA, identified two differentially spliced isoforms of mRNA with open r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
466
0
21

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 674 publications
(508 citation statements)
references
References 46 publications
(45 reference statements)
21
466
0
21
Order By: Relevance
“…5), our data indicated that virtually no NKT cells in the blood of children, or adults, expressed the Ki67 antigen expressed by proliferating cells (Fig. 5C) [26][27][28]. In contrast, a significant proportion of NKT cells in the thymus were Ki67 + (*5%), suggesting that a proportion of thymus NKT cells are cycling.…”
Section: Correlating Nkt Cell Levels In Human Thymus and Bloodmentioning
confidence: 86%
“…5), our data indicated that virtually no NKT cells in the blood of children, or adults, expressed the Ki67 antigen expressed by proliferating cells (Fig. 5C) [26][27][28]. In contrast, a significant proportion of NKT cells in the thymus were Ki67 + (*5%), suggesting that a proportion of thymus NKT cells are cycling.…”
Section: Correlating Nkt Cell Levels In Human Thymus and Bloodmentioning
confidence: 86%
“…The antigen Ki-67 is a non-histone nuclear protein of unknown function, although its direct role in the maintenance of cell proliferation has been demonstrated by the inhibition of DNA synthesis by specific antisense oligonucleotides for Ki-67 mRNA (Schluter et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 is expressed at relatively low levels in GI and early S-phase; it rapidly accumulates during the second half of S-phase, reaching a peak at GI`M phases and decreases sharply in post-mitotic cells (Gerdes, 1984;Bruno and Darzynkiewicz, 1990). Being expressed in all the cycle phases, Ki-67 is a particularly suitable marker for proliferating cells (Gerdes et al, 1984;Schluter et al, 1993), and it may therefore be preferred in cell kinetic studies to other proliferation markers, such as cyclins, whose expression is limited to well-defined phases or even subphases of the cycle (Gong et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic and blood vessels are examined by using mouse monoclonal D2-40 antibody (Abcam, Cambridge, UK) and mouse monoclonal anti-CD31 antibody (Dako, Denmark), respectively. These antibodies are well characterized and have been used in many previous studies [27,[34][35][36][37][38][39]. Serial sections of 5 μm were cut from formalin-fixed paraffin-embedded tissue blocks, deparaffinized in xylene and hydrated in a series of graded alcohols (100 %, 95 %, and 70 %).…”
Section: Antibodies and Immune-staining Of Tissue Sectionsmentioning
confidence: 99%